Quantum Dot Sensitized Solar Cells Based on TiO2/AgInS2 - Pawar, Sachin A.; Jeong, Jae Pil; Patil, Dipali S.; More, Vivek M.; Lee, Rochelle S.; Shin, Jae Cheol; Choi, Won Jun (KOREAN PHYSICAL SOC, 2018)
Quantum dot heterojunctions with type-II band alignment can efficiently separate photogenerated electron-hole pairs and, hence, are useful for solar cell studies. In this study, a quantum dot sensitized solar cell (QDSSC) made of TiO2/AgInS2 is achieved to boost the photoconversion efficiency for the TiO2-based system by varying the AgInS2 layer's thickness. The TiO2 nanorods array film is prepared by using a simple hydrothermal technique. The formation of a AgInS2 QD-sensitized TiO2-nanorod photoelectrode is carried out by successive ionic layer adsorption and reaction (SILAR) technique. The effect of the QD layer on the performance of the solar cell is studied by varying the SILAR cycles of the QD coating. The synthesized electrode materials are characterized by using X-ray diffraction, X-ray photoelectron spectroscopy, field emission scanning electron microscopy, high resolution transmission electron microscopy and solar cell performances. The results indicate that the nanocrystals have effectively covered the outer surfaces of the TiO2 nanorods. The interfacial structure of quantum dots (QDs)/TiO2 is also investigated, and the growth interface is verified. A careful comparison between TiO2/AgInS2 sensitized cells reveals that the trasfer of electrons and hole proceeds efficiently, the recombination is suppressed for the optimum thickness of the QD layer and light from the entire visible spectrum is utilised. Under AM 1.5G illumination, a high photocurrent of 1.36 mAcm(-2) with an improved power conversion efficiency of 0.48% is obtained. The solar cell properties of our photoanodes suggest that the TiO2 nanorod array films co-sensitized by AgInS2 nanoclusters have potential applications in solar cells.
Keywords: CDS